Analisis Kesehatan Keuangan dan Implikasinya Terhadap Profitabilitas BPR - Budi Santoso; Sunarto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research aims to analyze CAR, NPL, BOPO and LDR on profitability in BPRs in the Semarang city area. The population of this research is the quarterly financial reports of BPR Semarang city for the 2019-2022 period. The sample in this research is the quarterly financial report of BPR Semarang city. Using the convenience sampling technique, a research sample of 82 observations of quarterly financial reports was obtained. The analysis technique uses multiple linear regression. The results show that CAR has no positive effect on ROA, while NPL and BOPO have a negative effect on ROA, and LDR has a positive effect on ROA. The results of this research can be used by OJK to help maintain financial system stability and protect customers by increasing the effectiveness of supervision. Apart from that, it can also formulate more effective policies in encouraging the growth and profitability of BPR, so that ultimately it can increase public trust in the financial sector.